After Older Adult Maltreatment: Service Needs and Barriers. Issue 7 (3rd October 2019) - Olomi, Julie M.; Wright, Naomi M.; Hasche, Leslie; DePrince, Anne P.
ABSTRACT: Little research is available specific to the service needs or related barriers of maltreated older adults. Further, no studies have asked at-risk older adults directly for their perspectives on service needs and barriers. As part of a larger study, a sample of 40 diverse older adults ( M age = 76 years) were recruited from the population of older adults who were involved in an abuse, neglect, and/or financial exploitation case where the offender was in a position of trust to the victim. Responses to open-ended questions about participants' service needs and reasons for not seeking services were thematically coded. The majority of older adults expressed needing more help than currently received, with needs including transportation, housing, food, household assistance, and medical and mental health care. Participants also described reasons their service needs were not being met. The study elaborates on the specifics and descriptive statistics of the themes that emerged. Implications for older-adult victim services, as well as broader older-adult services, are discussed.